2019
DOI: 10.1109/access.2019.2940910
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Human Data-Driven Model Based on Machine Learning for Prediction of Human Comfort

Abstract: Occupants' comfort level has a strong correlation with health problems. Providing a comfortable environment for the occupants will bring the benefits of improved health. To achieve this goal, it is necessary to have a reliable human comfort model for predicting the occupants' comfort level and subsequently controlling the involved comfort condition. However, the comfort perception of occupants is subjective. There is a lack of objective indices for measuring comfort level. Furthermore, human comfort is affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…They concluded that the alternating decision tree model was the superior model for the considered task. Mao et al 23 performed experiments to predict human comfort. They employed support vector regression with a radial basis function kernel, and compared the obtained results with linear regression, forms of ridge regression, support vector regression with linear kernel and multi-layer perceptron.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the alternating decision tree model was the superior model for the considered task. Mao et al 23 performed experiments to predict human comfort. They employed support vector regression with a radial basis function kernel, and compared the obtained results with linear regression, forms of ridge regression, support vector regression with linear kernel and multi-layer perceptron.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…For this reason, several comparative studies have been performed to determine superior ML models for prediction problems. [22][23][24] However, researchers have concluded that there is no single model that is superior for all kinds of prediction or classification problems and also different researchers have determined different ML models to be superior in different experiments.…”
Section: Machine Learning Modelsmentioning
confidence: 99%